A Call to Cultivate the Public Interest: Beyond Pro Bono - Ann Juergens; Diane Galatowitsch (Washington University Journal of Law & Policy, 2016)
This Article scrutinizes the transformation of the legal profession from lawyers as public citizens to lawyers who serve mostly private interests. Juergens and Galatowitsch trace the development of current pro bono practices and how these practices have become equated with public service. Juergens and Galatowitsch argue that current pro bono practices have narrowed the definition of “public interest law work” and conclude that an expansion of the term’s definition is necessary to promote its practice in the current legal environment.
Keywords: Public Interest; Pro Bono; Legal profession; War on Poverty; Office of Economic Opportunity; Legal Services Program; American Bar Association